A Deep Dive into Stellar Populations in M33’s Central Region: Near-Infrared Observations and Analysis - Mina Alizadeh; Atefeh Javadi; Jacco Th. van Loon; Yousefali Abedini; Hedieh Abdollahi; Sarina Seifipour
Data collection was conducted using three cameras on the UK Infrared Telescope (UKIRT) from 2003 to 2007. Throughout three nights in August 2005, the UKIRT Fast-Track Imager (UFTI) made K-band observations. The J and H bands Wide Field Camera (WFCAM) data were gathered from 2005 to 2007. Furthermore, from 2003 to 2007, UIST data for the central region of M33 were collected in the K-band. Since luminosity is more closely correlated with birth mass in the latter stages of a star’s evolution, we concentrated on these stars. We will combine all the PSF photometry catalogs of the UIST, the UFTI, and the WFCAM to present a novel master catalog of the central square kiloparsec to re-identify the LPV populations. By having more data points for each point source, the probability of detecting more LPVs goes up; also, a period might be derived for some. In addition to that, the SFH will be estimated more accurately by having a larger sample of variable stars.
Keywords: Stars